2021
DOI: 10.1037/sgd0000514
|View full text |Cite
|
Sign up to set email alerts
|

Training mental health providers in queer-affirming care: A systematic review.

Abstract: The effectiveness of training for mental health professionals to increase queer-affirming (e.g., lesbian, gay, bisexual, pansexual) cultural competencies has not been well established. Though there is an assumption that training generally works to increase or improve knowledge, attitudes, and skills, it is unclear what training format, content, and pedagogical approaches are effective. To explore the effectiveness of cultural competency training interventions for mental health professionals, a systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
(127 reference statements)
1
23
0
Order By: Relevance
“…The findings of Bettergarcia et al (2021) empirically validate the intuitive sense many of us already had, that is, that an analysis of the relevant articles generated more questions than they answered, and that there is no gold (or even silver or bronze) standard for trainings on providing queer-affirmative care in terms of content, modality, length, or audience. On one hand, these findings are disappointing.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…The findings of Bettergarcia et al (2021) empirically validate the intuitive sense many of us already had, that is, that an analysis of the relevant articles generated more questions than they answered, and that there is no gold (or even silver or bronze) standard for trainings on providing queer-affirmative care in terms of content, modality, length, or audience. On one hand, these findings are disappointing.…”
supporting
confidence: 57%
“…We commend Bettergarcia et al (2021) on their thoughtful and thorough systematic review on mental health provider trainings in queer-affirming care. Prior published reviews have focused on sexual and gender minority-affirming therapies (O’Shaughnessy & Speir, 2018) but fewer have focused on the training needed to implement those therapies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In their comprehensive analysis, Velez et al (2021) identified neglected populations within sexual minority communities (e.g., persons of color, sexual and gender minority youth), understudied vocational contexts (e.g., unemployed populations, hiring practices), and limitations to research methodologies, and they offer fruitful directions for future research and intervention. Bettergarcia et al (2021) recognized the importance of professional training and education in the field of psychology. They conducted a systematic review of empirical scholarship published within a span of 20 years, exploring process and outcomes associated with queer cultural competency training for mental health practitioners.…”
Section: Organization and Content Of The Special Issuementioning
confidence: 99%